2010
DOI: 10.1002/cncy.20110
|View full text |Cite
|
Sign up to set email alerts
|

Should adequacy criteria in cervicovaginal cytology be modified after radiotherapy, chemotherapy, or hysterectomy?

Abstract: BACKGROUND. The general criterion of an unsatisfactory Papanicolaou (Pap) test in the 2001 version of the Bethesda system is not applicable to patients after treatment with radiotherapy, chemotherapy, or hysterectomy. The current study was performed to determine whether specimen adequacy criteria for Pap tests should be modified for these conditions. METHODS. Consecutive patients who underwent conventional Pap tests between March and August 2006 were reviewed. The original reports were done according to the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…In addition, cellular degeneration and debris, particularly in cases of atrophic vaginitis, adds to the difficulty. In their study, Lu et al reported that age greater than 50 years was associated with a statistically significant, but only slight increase in the unsatisfactory rate as compared to women under 50 years of age.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, cellular degeneration and debris, particularly in cases of atrophic vaginitis, adds to the difficulty. In their study, Lu et al reported that age greater than 50 years was associated with a statistically significant, but only slight increase in the unsatisfactory rate as compared to women under 50 years of age.…”
Section: Discussionmentioning
confidence: 90%
“…The survey also reported that 79% of the participating laboratories applied minimum squamous epithelial cell adequacy criteria to atrophic and/or post‐irradiation specimens; however, it was not possible to ascertain from the responses whether the laboratories modified the minimum squamous epithelial cellularity criteria for women falling into these clinical categories. Using the 2001 Bethesda System criteria for specimen adequacy, Lu et al reported a higher incidence of scant cellularity on conventional pap smears from patients who received radiation and/or chemotherapy. In this group of patients, the unsatisfactory rate was 13.2%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a cytopathologist with little experience in this area may underestimate the changes, missing the opportunity to detect early or recurrent cancer. 19,[29][30][31] Persistent or recurrent carcinoma is diagnosed in the cervicovaginal smear when malignant cells are identified in the course of radiotherapy or immediately after its completion. It indicates radioresistance of the neoplastic cells, being thus related to a poorer prognosis.…”
Section: Post-radiotherapy Effects On Cellsmentioning
confidence: 99%
“…The most reliable criterion to establish the viability of neoplastic cells is the finding of mitoses. 26,27,34 Since radiotherapy is associated with characteristic cytological changes, including nuclear activation, increased cytoplasm (with preservation of the nuclear-cytoplasmic ratio), cytoplasmic vacuolization, eosinophilia, polychromasia, multinucleated giant cells, nuclear membrane blebbing and nuclear vacuolization, as well as repair cells, atypical stromal cells, endothelial cells and macrophages, 29,31,35 cytological samples should be collected a few months after radiotherapy. However, it is true that radiotherapy is associated with unsatisfactory samples.…”
Section: Post-radiotherapy Effects On Cellsmentioning
confidence: 99%
See 1 more Smart Citation